On the influence of precessional Milankovitch cycles on the late cretaceous climate system: Comparison of GCM-results, geochemical, and sedimentary proxies for the Western Interior Seaway of North America - Flögel, Sascha (Christian-Albrechts-Universität zu Kiel, 2002)
A multidisciplinary study of upper Cenomanian-lower Turonian strata of the late Cretaceous Western Interior Seaway explored possible mechanisms for the formation of cyclic bedding sequences seen in the Western Interior Seaway. Numerical climate modeling was used to investigate the sensitivity of the climate to changes of one of the Earth's orbital parameters, the precession of the equinoxes. One complete precessional cycle was simulated with four orbital runs; 1) northern spring equinox at perihelion, 2) northern winter solstice at perihelion, 3) northern fall equinox at perihelion, and 4) northern summer solstice at perihelion. The cyclic organization of limestone/shale couplets seen in the sedimentological record of the central part of the Western Interior Seaway can be interpreted as reflecting climatic cycles. The most important mechanism for the formation of bedding couplets were changes induced by the precession of the equinoxes. The most important variable was surface runoff, which affected both the discharge of rivers and the amount of sediment transported into the Western Interior Seaway. Annual river discharge from western North America into the seaway was equivalent to a layer of fresh water ~0.3m thick. River discharge into the Arctic Ocean was even greater, equivalent to a layer more than 1m thick each year. These very large supplies of fresh water from land were adequate to maintain low salinity surface waters in the Arctic Ocean and the Western Interior Seaway. High surface runoff from the highlands bordering the Western Interior Seaway to the west occured during summer in three of the orbital configurations but low surface runoff when northern hemisphere winter is at perihelion. The precession signal seen in the sediment is interpreted as being produced by the elimination of high summer surface runoff when perihelion occurs during northern hemisphere winter.